Kinerja struktural Interlocking Compressed Earth Block (ICEB) dengan serta ijuk sebagai stabilisator - Budianastas Prastyatama; Anastasia Maurina (ARTEKS : Jurnal Teknik Arsitektur, 2018)
Modular block building materials have been well-known in the design and construction of built-environment. In its simplest form, the modular block is known as brick, red brick, lime brick, conblock, etc. The modularity of its unit lends itself for easy of production, application and transport. The drawbacks, however, are the generallyrelated to high energy consumption and pollution level in the production process (brick burning, high temp heating of cement and lime). In the perspective of sustainable and environmentally friendly built environment, the drawbacks need to be addressed in order to minimize its carbon footprint in human habitation. The challenge is how to obtain modular blocks with low energy consumption, while achieving stability and structural performance up to the standard. In this research, the earthen block test units were conducted without burning or use of cement and lime. Ijuk fibre (Arenga pinnata) was chosen as replacement of cement and lime was choses as stabilizer in producing modular blocks. The main test units and their comparisons underwent a compression test in the compressive testing machine to evaluate the structural performance. The comparison test blocks were blocks with similar form, dimension and production method, while the diffrentiating factor was the mixture. The standards SNI 15-2094-2000 (Indonesia) and IS 1077 : 1992 (India) were used as reference to compressive strength of common fired brick. © 2018 Budianastas Prastyatama, Anastasia Maurina